Edukasi dan Implementasi Zakat, Infak, Sedekah, dan Wakaf Produktif Bagi Jama’ah Masjid Al-Munawwarah - Samsuri, Samsuri; , Warto, , Warto; Aurellia , Amanda; Yuliadi, Iqbal (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2024)
The purpose of this education is to increase Muslims' understanding of the urgency of zakat to be able to be involved in ZISWAF. Held once a week, 60 minutes per session at the Al Munawwarah Mosque from 1-30 May 2024 with 50 participants. The lecture presented consisted of 4 modules with a lecture format with interactive discussion. As a result of this education, most of the congregation understands the urgency of ZISWAF and has the desire to play an active role in ZISWAF.